2019
DOI: 10.1039/c9tx00048h
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitions of HMGB1 and TLR4 alleviate DINP-induced asthma in mice

Abstract: We studied the effects of high mobility group box chromosomal protein 1 (HMGB1) and toll-like receptor (TLR4) in diisonoyl phthalate (DINP)-induced asthma. Mice with DINP-induced asthma were treated with a TLR4-signaling inhibitor or anti-HMGB1 antibody, and various markers of asthma were measured 24 h later. DINP increased airway hyperresponsiveness, numbers of cells in BALF, numbers of inflammatory cells (leukocytes, lymphocytes, monocytes, eosinophils, neutrophils, basophils) in blood, mucus production, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Inadequate regulation of the TLR4 signaling contributes to the pathogenesis of a number of acute and chronic inflammatory as well as autoimmune diseases such as allergy, arthritis (7)(8)(9), asthma (10)(11)(12), cardiovascular disorders (13), Alzheimer disease-associated pathology (14) and systemic inflammatory response syndrome (SIRS) and septic shock (15,16). Impressive research demonstrated that down-regulation of the TLR4 mediated signaling can be useful for therapeutic benefits and efficient for management of asthma (17,18), arthritis, (8) viral infections [influenza (19) and Ebola virus (20)], cancer (21), and sepsis (22). Besides, TLR4-mediated signaling has been demonstrated to promote dendritic cells maturation thereby linking innate and adaptive immunity (23,24) which features activation of the TLR4/MD-2 complex by TLR4-specific ligands of low toxicity as facile approach for development of novel vaccine adjuvants (25)(26)(27).…”
Section: Lipopolysaccharide Detection By the Innate Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate regulation of the TLR4 signaling contributes to the pathogenesis of a number of acute and chronic inflammatory as well as autoimmune diseases such as allergy, arthritis (7)(8)(9), asthma (10)(11)(12), cardiovascular disorders (13), Alzheimer disease-associated pathology (14) and systemic inflammatory response syndrome (SIRS) and septic shock (15,16). Impressive research demonstrated that down-regulation of the TLR4 mediated signaling can be useful for therapeutic benefits and efficient for management of asthma (17,18), arthritis, (8) viral infections [influenza (19) and Ebola virus (20)], cancer (21), and sepsis (22). Besides, TLR4-mediated signaling has been demonstrated to promote dendritic cells maturation thereby linking innate and adaptive immunity (23,24) which features activation of the TLR4/MD-2 complex by TLR4-specific ligands of low toxicity as facile approach for development of novel vaccine adjuvants (25)(26)(27).…”
Section: Lipopolysaccharide Detection By the Innate Immune Systemmentioning
confidence: 99%
“…One of the plausible mechanisms for LPS internalization and intracellular delivery involves LPS binding by high-mobility group box 1 (HMGB1) -an alarmin which can efficiently transport LPS into the cytoplasm through receptor for advanced glycation end products (RAGE)-mediated endocytosis (17,135,136). Through internalization of HMGB1-LPS complexes mediated by RAGE, HMGB1 induces destabilization of lysosomes for cytosolic LPS delivery.…”
Section: Cytosolic Delivery Of Lps For Noncanonical Inflammasome Actimentioning
confidence: 99%
“…Toll like receptor signaling pathway was activated in patients in the exacerbation group. In fact, the complex interaction between environmental allergens and TLRs results in In the hub genes, TLR4 was reported to be signi cantly associated with the occurrence and development of asthma (Hwang, et al 2019). Heat shock protein (HSP) played a major role in promoting in ammation and anti-in ammatory response (Hallenbeck and Kaplan 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting HMGB1 may a useful treatment for asthma. HMGB1 antagonists repressed leukocyte infiltration, levels of collagen, cell counts and pro-inflammatory cytokines in animal models, which attenuated airway remodeling and airway hyperresponsiveness [ 204 , 205 , 206 ].…”
Section: Role Of Hmgb1 In Various Inflammatory Disordersmentioning
confidence: 99%